(untitled) (Current Horticulture, 2024)
The studies were carried out to evaluate five wild banana (Musa spp.) and three hybrids for morphological characters and their suitability of ornamental value based on 12 quantitative and 6 qualitative traits at NRC for Banana, Tiruchirappalli, during 2016-17. The results showed that all the eight species varied significantly for all the traits. The wild were dwarf (<1.0 m height) and slender (<20 cm stem girth) and recorded an average of 7-9 leaves/plant. The hybrids were larger (>1.0 m height) and little sturdy (>30.0 cm stem girth). The wild bananas recorded an average of 4 hands/bunch and 4 fruits/hand while hybrids recorded more than 4 hands/bunch and 10 fruits/hand. The inflorescence was erect and bract colour ranged from lilac, brick-red, red, yellow and pink. Based on the study, the wild bananas were highly suitable for potted plants, cut flowers, male inflorescence, and landscape plants while hybrids were suitable only for landscape purposes.